Event: Strategies of Tourism Development in Primorsky Krai (Russia) - Martyshenko, Natalya Stepanovna; Kim, Angelina Georgievna (International Review of Management and Marketing, 2017)
Primorsky Krai with its rich natural tourism potential hasn't yet found its place in the international market, so event-marketing can help to solve this problem. The impact of mass events may occur as an indirect and direct inclusion in the program of the tour. In this work there are examples of public events in the Primorsky region, which have a significant international impact and, moreover, tend to grow in popularity among tourists. The largest international exercise, which had opened a new page in the development of the Russian Far East was the APEC Summit, which was held in Vladivostok in September 2012. Keywords: event-strategy, the international tourist market, Festival JEL Classifications: L83, Z32